Kinetics of ferroelectric domains investigated by scanning force microscopy - V. Likodimos; Labardi, M.; Allegrini, M. (Physical Review B - Condensed Matter and Materials Physics, 2000)
Voltage-modulated scanning force microscopy has been applied to investigate domain kinetics in triglycine sulfate single crystals, thermally quenched from the paraelectric to the ferroelectric phase. Temporal analysis of the equal-time correlation functions shows that the average domain size grows initially with a power law dependence close to that of conserved systems, whereas a crossover to the slower logarithmic growth law (Formula presented) predicted for systems with random impurities occurs in the late stage of coarsening. Domain growth is dominated by a single characteristic length scale consistent with the dynamical scaling hypothesis. The total surface charge corresponding to the domain area of the two polarization states is found to be conserved within the studied time scale, indicating that the system may be considered to behave like one with conserved order parameter. © 2000 The American Physical Society.